Pengaruh Penerapan Model Pembelajaran Picture and Picture yang dipadukan Dengan Strategi Pembelajaran Aktif Tipe Everyone is a Teacher here Terhadap Hasil Belajar Biologi: (The Effect of the Application of the Picture and Picture Learning Model combined with the Active Learning Strategy Type Everyone is a Teacher here on Biology Learning Outcomes) - Ali Sadikin (BIODIK, 2020)
This study aims to determine the effect of applying of the use of Picture and Picture learning model combined with learning strategy Everyone Is A Teacher Here on the results of biology 11th Grade StudentsÂ  This research was conducted at Senior High Scholl No.1 Muaro Jambi, in 2016/2017. This type of research is a True experiment. The sample used consists of 2 classes, namely experimental class and control class. The treatment was done in the experimental class by applying the Picture and Picture learning model combined with the learning strategy of Everyone Is A Teacher Here, while in the control class applying the appropriate learning model in Senior High Scholl No.1 Muaro Jambi. The data collection using the test instrument is a multiple choice question, the questionnaire is adjusted to three aspects of the learning outcomes is cognitive, affective, and psychomotor aspects and has been tested for validity and reliability. Can be seen the average value of the cognitive aspects of the experimental class gained 72.52 Â and control class gained 64,13. Hypothesis tests tarithmatic = 4,55 and a ttable = 1.671, this means tarithmetic> ttable so the hypothesis is accepted. On the affective aspects of the experimental class 80,48 and control class gained 76,19. Hypothesis tests tarithmatic= 1,981 and a value table = 1.671, this means tarithmetic> ttable so the hypothesis is accepted. In the aspect of psychomotor experimental class gained 80,90 and control class gained 63,03. Hypothesis tests t tarithmatic = 4,38 and ttable= 1.671, this means tarithmetic> ttable so the hypothesis is accepted. From these results it can be concluded that the application Model of Picture and Picture learning combined with Active Learning strategy Everyone Is A Teacher Here on student learning result on cognitive, affective and psychomotor aspects. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan penggunaan model pembelajaran Picture and Picture yang dipadukan dengan strategi pembelajaran Everyone Is A Teacher Disini terhadap Hasil Biologi Siswa Kelas XI Penelitian ini dilakukan di SMA Negeri No 1 Muaro Jambi, di 2016/2017. Jenis penelitian ini adalah Eksperimen Sejati. Sampel yang digunakan terdiri dari 2 kelas yaitu kelas eksperimen dan kelas kontrol. Perlakuan dilakukan di kelas eksperimen dengan menerapkan model pembelajaran Picture and Picture yang dipadukan dengan strategi pembelajaran Everyone Is A Teacher Here, sedangkan di kelas kontrol menerapkan model pembelajaran yang sesuai di SMA No 1 Muaro Jambi. Pengumpulan data menggunakan instrumen tes berupa soal pilihan ganda, angket disesuaikan dengan tiga aspek hasil belajar yaitu aspek kognitif, afektif, dan psikomotor serta sudah diuji validitas dan reliabilitasnya. Dapat dilihat nilai rata-rata aspek kognitif diperoleh kelas eksperimen 72,52 dan kelas kontrol memperoleh 64,13. Uji hipotesis taritmatik = 4,55 dan ttabel = 1,671, ini berarti thitung> t tabel sehingga hipotesis diterima. Pada aspek afektif kelas eksperimen 80,48 dan kelas kontrol memperoleh 76,19. Uji hipotesis taritmatik = 1,981 dan nilai tabel = 1,671, ini berarti thitung> ttabel sehingga hipotesis diterima. Pada aspek psikomotorik kelas eksperimen memperoleh 80,90 dan kelas kontrol memperoleh 63,03. Uji hipotesis t thitung = 4,38 dan ttabel = 1,671, ini berarti thitung> ttabel sehingga hipotesis diterima. Dari hasil tersebut dapat disimpulkan bahwa penerapan Model Pembelajaran Picture and Picture yang dipadukan dengan strategi Active Learning Everyone Is A Teacher Here terhadap hasil belajar siswa pada aspek kognitif, afektif dan psikomotorik.